Emotional Lability as a Unique Presenting Sign of Suspected Chronic Traumatic Encephalopathy - Shauna H. Yuan; Sonya G. Wang (Case Reports in Neurological Medicine)
Chronic traumatic encephalopathy (CTE) is a neurodegenerative disease caused by head trauma. Diagnosis of this disease is difficult as reliable biomarkers have not been established and often this clinical entity is underappreciated with poor recognition of its clinical presentations (Lenihan and Jordan, 2015). The definitive diagnosis of CTE is determined by identification of neurofibrillary tangles in the perivascular space around the sulci in postmortem tissue (McKee et al., 2015). However, performing brain biopsies searching for neurofibrillary tangles is not a feasible option for early diagnosis. Thus, diagnosis of suspected CTE in the living has been based on clinical suspicion using proposed research criteria of clinical presentations. In addition, neuroimaging techniques have shown some promise in assisting diagnosis. Clinically, CTE is more commonly known to be associated with memory impairment and executive function disorder (Stern et al., 2013). However, here, we present two unique cases of prior professional football players where behavioral changes were the first identifying factors in clinical presentation and discuss possible neuroimaging options to help with CTE diagnosis. Because behavioral changes can be mistaken for other neuropsychological diseases, recognizing differing clinical constellations is critical to early diagnosis, early intervention, and improving patient care in suspected CTE.